Assessing the Impact of Sustainable Independent Oil Palm Cultivation on Rural Development: A Case Study of Angkola Sangkunur Sub-District, South Tapanuli Regency - Lubis, Arga Abdi Rafiud Darajat; Marpaung, Henry (CV. ARGA FARMA, 2024)
This study evaluates the impact of sustainable independent oil palm cultivation on rural development in the Angkola Sangkunur sub-district, South Tapanuli Regency, Indonesia. The research focuses on five key aspects: legal, technical cultivation, environmental management, labor, and institutional factors. Data was collected through a combination of primary and secondary sources, with primary data obtained via questionnaires distributed to a probability-based sample of 165 respondents. The analysis employed multiple linear regression to assess the influence of each aspect on regional development, with hypotheses tested using both F-tests and t-tests. The results reveal that the technical cultivation and institutional aspects exert a significant positive influence on rural development, underscoring the critical role of advanced agricultural practices and strong governance structures. While legal and environmental management aspects also have positive effects, their impact was not statistically significant, indicating that these factors may require further development or longer timeframes to manifest significant outcomes. Conversely, the labor aspect showed a negative but statistically insignificant effect, suggesting that the costs associated with implementing sustainable labor practices may pose challenges for smallholder farmers. This study concludes that enhancing technical capabilities and institutional frameworks offers the most immediate and substantial benefits for rural development in the region. However, a holistic approach that also addresses legal, environmental, and labor issues is essential for achieving long-term sustainability. The findings provide valuable insights for policymakers, stakeholders, and researchers focused on sustainable agriculture and rural development.